2014
DOI: 10.1080/17461391.2014.944875
|View full text |Cite
|
Sign up to set email alerts
|

Generic anthropometric and performance characteristics among elite adolescent boys in nine different sports

Abstract: The aim of the present study was to evaluate the Flemish Sports Compass (FSC), a non-sport-specific generic testing battery. It was hypothesised that a set of 22 tests would have sufficient discriminant power to allocate athletes to their own sport based on a unique combination of test scores. First, discriminant analyses were applied to the 22 tests of anthropometry, physical fitness and motor coordination in 141 boys under age 18 (16.1 ± 0.8 years) and post age at peak height velocity (maturity offset = 2.67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 32 publications
4
45
0
4
Order By: Relevance
“…The reliability of effective tools for assessing physical performance in sport and educational systems is important, especially when sports authorities, clubs, federations and professionals aim to find young sports talents for a variety of sports or when designing talent identification programs (Bergeron et al, 2015; Johnston, Wattie, & Schorer, 2017; Pion, Segers, et al, 2015). To the best of our knowledge, no other research has reported the reliability of a physical fitness battery among young athletes from different sports and different levels of competition.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of effective tools for assessing physical performance in sport and educational systems is important, especially when sports authorities, clubs, federations and professionals aim to find young sports talents for a variety of sports or when designing talent identification programs (Bergeron et al, 2015; Johnston, Wattie, & Schorer, 2017; Pion, Segers, et al, 2015). To the best of our knowledge, no other research has reported the reliability of a physical fitness battery among young athletes from different sports and different levels of competition.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of gifted athletes are also very specific. Different sports (Pion et al, 2015), or even different playing positions within a team sport (Pion et al, 2018), require different abilities or at least a different combination of them. Therefore, a "one size fits all" consensus for talent identification in sports is not possible.…”
Section: Talent Identification In Youth Sportmentioning
confidence: 99%
“…However, in many sports a specific height is not a clear advantage (e.g. badminton, field hockey, table tennis, soccer) (Elferink-Gemser, Visscher, Lemmink, & Mulder, 2004;Keogh, Weber, & Dalton, 2003;Pion et al, 2015;Reilly, Bangsbo, & Franks, 2000). The athletes' profiles might differ even at the highest competition level using strengths to compensate for weaknesses; for example, within the world's top 10 ranking in CISS 4 (2019) May 2019 I Article 103 I 17 badminton (January 2019) height differs from 1.75 m to 1.94 m between men and from 1.56 m to 1.79 m for women (https:// bwfbadminton.com/rankings/).…”
Section: Open Accessmentioning
confidence: 99%
“…CISS 4 (2019) May 2019 I Article 103 I 18 Pion, J., Segers, V., Fransen, J., Debuyck, G., Deprez, D., Haerens, L., ... & Lenoir, M. (2015). Generic anthropometric and performance characteristics among elite adolescent boys in nine different sports.…”
Section: Open Accessmentioning
confidence: 99%